Sosialisasi Pengaruh Kualitas Layanan dan Kepuasan Konsumen Terhadap Loyalitas Konsumen pada Perusahaan Jasa Perjalanan Wisata Mojopahit Tour & Travel di Mojokerto - Nanang Andhiyan Mergining Mei; Wahyu Adhafiya; Maersa Berlina Putri Rifai (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The high number of domestic (domestic) tourists increases competition between travel entrepreneurs in providing satisfaction to consumers. Satisfied consumers will recommend to others. This is what is called loyalty. Between service quality, customer satisfaction and loyalty are a series. Majapahit tour & travel as one of the travel service providers does not yet know the relationship and influence between service quality, consumer satisfaction and consumer loyalty. The problem that partners often encounter is a lack of understanding of the service quality factors that determine consumer satisfaction and loyalty to their business so that partners only carry out routine activities. The importance of service quality is proven by research which is followed by outreach to partners so that partners better understand and know which parts to focus on to provide more satisfaction to consumers.